ETHNIC AND CIVILIAN IN THE CONTEXT OF MODERNIZATION OF NATIONAL IDENTITY - Alaverdyan, N. A. (Modern Psychology, 2019)
The national identity upkeep is the most important problem in the modern society there are many economic, social and cultural challenges and difficulties. This challenges seems are testing the systems of national identity, self and coexistence. The ethnocultural factor, which are carry out the uncertain and chaotic «traditional» values are leveled up using different models of political modernization. The national identity is formed as a value by the time in the domains of historical experience of several societies. At the same time the globalization is deeply transform the settings of national republics pro moving the problem of transformation also the national identity. So the problem of national identity gets full-face and hardly definition. Each national identity is a combination of historical, cultural and psychological factors. First of all, nation is characterized not by the state rolls, but by its historical, cultural and social heritage and with its consciousness.
Keywords: National identity, ethno-cultural, socio culture transformation, challenges, national value